Lipoarabinomannan mannose caps do not affect mycobacterial virulence or the induction of protective immunity in experimental animal models of infection and have minimal impact on in vitro inflammatory responses. (21st November 2012) - Afonso‐Barroso, António; Clark, Simon O.; Williams, Ann; Rosa, Gustavo T.; Nóbrega, Cláudia; Silva‐Gomes, Sandro; Vale‐Costa, Sílvia; Ummels, Roy; Stoker, Neil; Movahedzadeh, Farahnaz; van, Peter; Sloots, Arjen; et al.
Summary Mannose‐capped lipoarabinomannan (ManLAM) is considered an important virulence factor of Mycobacterium tuberculosis. However, while mannose caps have been reported to be responsible for various immunosuppressive activities of ManLAMobserved in vitro, there is conflicting evidence about their contribution to mycobacterial virulence in vivo. Therefore, we used Mycobacterium bovis BCG and M. tuberculosis mutants that lack the mannose cap of LAM to assess the role of ManLAM in the interaction of mycobacteria with the host cells, to evaluate vaccine‐induced protection and to determine its importance in M. tuberculosis virulence. Deletion of the mannose cap did not affect BCG survival and replication in macrophages, although the capless mutant induced a somewhat higher production of TNF. In dendritic cells, the capless mutant was able to induce the upregulation of co‐stimulatory molecules and the only difference we detected was the secretion of slightly higher amounts of IL‐10 as compared to the wild type strain. In mice, capless BCG survived equally well and induced an immune response similar to the parental strain. Furthermore, the efficacy of vaccination against a M. tuberculosis challenge in low‐dose aerosol infection models in mice and guinea pigs was not affected by the absence of the mannose caps in the BCG. Finally, the lack of the mannose cap in M. tuberculosis did not affect its virulence in mice nor its interaction with macrophages in vitro. Thus, these results do not support a major role for the mannose caps of LAM in determining mycobacterial virulence and immunogenicity in vivo in experimental animal models of infection, possibly because of redundancy of function.